Korelasi Atribut Produk Dan Performa Karyawan Terhadap Kepuasan Konsumen Fazza T&T - Sudirman, Rendy (Journal of Economic and Management (JECMA), 2023)
This study aims to determine the impact that product attributes and employee performance have on customer satisfaction in companies in the tourism sector that are returning after the COVID-19 pandemic. The research method uses associative quantitative methods with data collection methods using questionnaires to Fazza Tour and Travel consumers, with as many as 300 respondents through accidental sampling techniques during May–July 2023. Meanwhile, the hypothesis analysis uses Spearman's rank correlation analysis. The results showed that product attributes had a positive and significant effect on customer satisfaction as evidenced by a correlation value of 0.791 and a significance value below 5%, which meant that the correlation was in the strong category, and employee performance had a positive and significant effect on customer satisfaction as evidenced by a correlation value of 0.672 and a significance value below 5%, which meant that the correlation was in the strong category.